Steroid profiling in pregnancy: a focus on the human fetus - Hill, Martin; Pašková, Andrea; Kančeva, Radmila; Velíková, Marta; Kubátová, Jana; Kancheva, Lyudmila; Adamcová, Karolína; Mikešová, Michaela; Žižka, Zdeněk; Koucký, Michal; Šarapatková, Hana; Kačer, Viktor; et al. (The Journal of steroid biochemistry and molecular biology, 2014)
In this review we focused on steroid metabolomics in human fetuses and newborns and its role in the physiology and pathophysiology of human pregnancy and subsequent stages of human life, and on the physiological relevance of steroids influencing the nervous systems with regards to their concentrations in the fetus. Steroid profiling provides valuable data for the diagnostics of diseases related to altered steroidogenesis in the fetal and maternal compartments and placenta. We outlined a potential use of steroid metabolomics for the prediction of reproductive disorders, misbalance of hypothalamic-pituitary-adrenal axis, and impaired insulin sensitivity in subsequent stages of human life. A possible role of steroids exhibiting a non-genomic effect in the development of gestational diabetes and in the neuroprotection via negative modulation of AMPA/kainate receptors was also indicated. Increasing progesterone synthesis and catabolism, declining production of tocolytic 5β-pregnane steroids, and rising activities of steroid sulfotransferases with the approaching term may be of importance in sustaining pregnancy. An increasing trend was demonstrated with advancing gestation toward the production of ketones (and 3β-hydroxyl groups in the case of 3α-hydroxy-steroids) was demonstrated in the fetus on the expense of 3α-hydroxy-, 17β-hydroxy-, and 20α-hydroxy-groups weakening in the sequence C17, C3, and C20. There was higher production of active progestogen but lower production of active estrogen and GABAergic steroids with the approaching term. Rising activities of placental CYP19A1 and oxidative isoforms of HSD17B, and of fetal CYP3A7 with advancing gestation may protect the fetus from hyperestrogenization. This article is part of a Special Issue entitled 'Pregnancy and Steroids'.
Keywords: vývoj plodu; Steroids; estrogeny; těhotenství; plod; mozek; Cord blood; Progestins; GC–MS; Fetal Development; progestiny; Metabolome; Brain; ženské pohlaví; zvířata; pohlavní steroidní hormony; Humans; Pregnancy; Estrogens; Labor; Gonadal Steroid Hormones; Fetus; hormony kůry nadledvin; Female; Adrenal Cortex Hormones; lidé; Animals